Soldiers on international missions : there and back again - Lyk-Jensen, Stephanie Vincent; Pedersen, Peder J. (Emerald, 2019)
This book investigates how the lives of soldiers deployed on international missions are affected during deployment and after returning home to family, work, and civilian life. Analyses are based on unique longitudinal data, comprehensive and deep interviews, making it possible to follow the impact of deployment on a broad range of life outcomes.